2013
DOI: 10.1088/0953-4075/46/13/134007
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bose gases with the Raman-induced spin–orbit coupling

Abstract: In this paper we investigate the properties of Bose gases with Raman-induced spin-orbit(SO) coupling. It is found that the SO coupling can greatly modify the single particle density-of-state, and thus lead to non-monotonic behavior of the condensate depletion, the Lee-Huang-Yang correction of groundstate energy and the transition temperature of a non-interacting Bose-Einstein condensate. The presence of the SO coupling also breaks the Galileaan invariance, and this gives two different critical velocities, corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
170
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(180 citation statements)
references
References 26 publications
7
170
1
Order By: Relevance
“…With the use of a physically straightforward variational method, ground states are demonstrated to include plane wave, stripe, and conventional BEC phases [41,43]. The full phase diagram can be labeled by various parameters, such as δ, Ω, and the nonlinear coefficients g [41,43,115]. Once the ground states are known, their collective excitations can be analyzed using the standard Bogoliubov-deGennes (BdG) equations.…”
Section: Bragg Spectroscopy Indicating Roton-like Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of a physically straightforward variational method, ground states are demonstrated to include plane wave, stripe, and conventional BEC phases [41,43]. The full phase diagram can be labeled by various parameters, such as δ, Ω, and the nonlinear coefficients g [41,43,115]. Once the ground states are known, their collective excitations can be analyzed using the standard Bogoliubov-deGennes (BdG) equations.…”
Section: Bragg Spectroscopy Indicating Roton-like Excitationmentioning
confidence: 99%
“…Once the ground states are known, their collective excitations can be analyzed using the standard Bogoliubov-deGennes (BdG) equations. It has been shown that the excitation spectrum of a plane wave phase features a rotonlike structure [23,[115][116][117]. The stripe phase, which is a superfluid phase with a broken continuous translational symmetry due to density crystallinity, exhibits an excitation spectrum comprised of two linear phonon modes [47].…”
Section: Bragg Spectroscopy Indicating Roton-like Excitationmentioning
confidence: 99%
“…Previous theoretical studies have described roton-like excitations of SOC BECs for the case of vanishing Raman detuning [17,18]. In our experiment, we measure mode softening when, starting from a finite value, the Raman detuning is decreased.…”
mentioning
confidence: 92%
“…Compared to the single-particle spectrum, the second minimum is modified due to the interaction energy, and for small excitation momenta the collective excitation spectrum becomes linear (phonon modes). The resulting dispersion is reminiscent of the phonon-maxon-roton like structure [16][17][18] Moreover, the presence of the nonlinearity leads to several phenomena within the collective excitation spectrum which are absent in the single-particle dispersion. One of the most fundamental of these is the softening of the roton-like modes when the spin-orbit coupling parameters are changed appropriately.…”
mentioning
confidence: 99%
“…The phase transition between the plane-wave and the striped phases has a first-order nature. It is charac- * Giovanni.Martone@ba.infn.it terized by the occurrence, on the side of the plane-wave phase, of a roton minimum in the excitation spectrum, whose energy becomes smaller and smaller as one approaches the transition [12][13][14]32]. The presence of the striped phase is one of the most interesting features exhibited by spin-orbit-coupled BECs, due to its direct link to the long sought phenomenon of supersolidity [33], which takes place when two continuous symmetries (gauge and translational invariance) are spontaneously broken.…”
Section: Introductionmentioning
confidence: 99%